Family of MnIII4LnIII2 (LnIII = SmIII, GdIII, DyIII) coordination clusters: Experimental and theoretical investigations. (24th November 2016) - Modak, Ritwik; Sikdar, Yeasin; Bieńko, Alina; Witwicki, Maciej; Jerzykiewicz, Maria; Goswami, Sanchita
Graphical abstract: A family of Mn III 4 Ln III 2 (Ln III = Sm III, Gd III, Dy III ) coordination clusters were synthesized utilizing a multisite hydroxyl rich ligand. The structural, topological and magnetic behaviors within the series were investigated extensively. DFT calculations afforded detailed insight into the magnetic exchange interactions between the Mn III and Gd III centers. Abstract: The present work introduces a family of Mn III 4 Ln III 2 (Ln III = Sm III, Gd III, Dy III ) coordination clusters having a multisite hydroxyl rich ligand, 3-[(2-hydroxy-3-methoxy-benzylidene)-amino]-propane-1, 2-diol (H3 Vapd), namely [Mn III 4 Sm III 2 (Vapd)4 (OAc)6 ]·4H2 O (1 ), [Mn III 4 Gd III 2 (Vapd)4 (OAc)6 ]·4H2 O (2 ) and [Mn III 4 Dy III 2 (Vapd)4 (OAc)6 ]·4H2 O (3 ). The Sm III analog is the first example of a Mn4 Ln2 species reported to date. The similarities and differences in terms of structure, topology and magnetic behaviors within the series are investigated extensively. DFT computations were carried out for Mn III 4 Gd III 2 to address the experimentally challenging questions regarding the nature of the magnetic interactions in this cluster.